The Effect Of Capital Structure On Profitability (A Study On Infrastructure Sector Companies Listed On The Indonesia Stock Exchange For The Period 2020–2024) - Desri Yanti Manalu; Andi Mustika Amin; Annisa Paramaswary Aslam (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The infrastructure sector plays a strategic role in Indonesia’s economic development due to its capital-intensive nature and long-term investment characteristics. Sound financial management, particularly in determining an optimal capital structure, is essential for maintaining profitability and ensuring sustainable growth. However, empirical evidence regarding the relationship between capital structure and profitability remains inconclusive, especially in the post-pandemic period. This study aims to examine the effect of capital structure on profitability in infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Capital structure is measured using the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Long-Term Debt to Total Assets (LTDtA), while profitability is proxied by Return on Assets (ROA). This research employs a quantitative approach using panel data from 39 infrastructure companies, resulting in 195 observations. Multiple linear regression analysis is applied to test both partial and simultaneous effects of the independent variables on profitability. Classical assumption tests, including normality, multicollinearity, and heteroskedasticity, are conducted to ensure the robustness of the regression model. The results of the F-test indicate that DAR, DER, and LTDtA simultaneously do not have a significant effect on ROA. However, the t-test reveals that LTDtA has a positive and significant effect on profitability, while DAR and DER show no significant influence. These findings suggest that overall leverage does not necessarily enhance profitability in infrastructure companies, but the appropriate use of long-term debt can improve performance through tax shield benefits and support long-term project financing. This study contributes to the literature by providing empirical evidence on capital structure decisions in Indonesia’s infrastructure sector during the post-pandemic period. The findings offer practical implications for corporate managers, investors, and policymakers in formulating effective financing strategies that balance financial risk and profitability.